Predictive Values of PET/CT in Combination With Regulatory B Cells for Therapeutic Response and Survival in Contemporary Patients With Newly Diagnosed Multiple Myeloma - Cui, Jian; Zou, Zhongqing; Duan, Jiayu; Tang, Wenjiao; Li, Yan; Zhang, Li; Pan, Ling; Niu, Ting (Frontiers in Immunology, 2021)
To assess patients with multiple myeloma (MM), the whole-body positron-emission tomography/computed tomography (PET/CT) occupies a pivotal position for diagnostic stratification, response evaluation, and survival prediction, while important limitations are recognized as incapable of representing tumor microenvironment. Regulatory B cells (Bregs) have been reported to have an inhibitory immune function, contributing to bone marrow (BM)-immunosuppressive microenvironment for MM. Therefore, to investigate the role of PET/CT in combination with Bregs’ ratios to predict therapeutic response and survival, we sequentially enrolled 120 patients with newly diagnosed MM (NDMM) who were treated with novel agents in our center, while conventional PET/CT parameters including maximum standard uptake value (SUVmax), ratios of BM-derived Bregs within CD19+ B cells, and patients’ clinical characteristics were collected. After a median follow-up of 28.20 months (range 7.00–46.93 months), SUVmax > 4.2 at onset, accounting for 53.2% of NDMM, was uncovered to predict inferior progression-free survival (PFS) as well as overall survival (OS). With regard to the ratios of BM-derived Bregs within CD19+ B cells, the cohort with the Bregs’ proportions lower than 10%, accounting for 46.2%, exerted poorer OS. Additionally, the patients with both SUVmax > 4.2 and Bregs’ ratios < 10%, accounting for 31.7%, yielded compromised therapeutic response and long-term survival. Collectively, this study may draw attention on the prognostic value of combination of PET/CT and Bregs’ ratios when clinical decisions are made for MM in the era of novel agents.